Translational insight into prothrombotic state and hypercoagulation in nonalcoholic fatty liver disease. Issue 198 (February 2021) - Ciavarella, Alessandro; Gnocchi, Davide; Custodero, Carlo; Lenato, Gennaro Mariano; Fiore, Giorgio; Sabbà, Carlo; Mazzocca, Antonio
Abstract: Non-alcoholic fatty liver disease (NAFLD) is an emerging and threatening pathological condition, ranging from fatty liver (FL) to chronic steatohepatitis (NASH), liver cirrhosis, and eventually to hepatocellular carcinoma (HCC). Recent findings suggest that patients with NAFLD have a higher risk of cardiovascular events and thromboembolism and that this risk is independent of metabolic diseases that are frequently associated with NAFLD, such as diabetes, hyperlipidaemia, and obesity. The vascular involvement of NAFLD might be considered its systemic burden, conditioning higher mortality in patients affected by the disease. These clinical findings suggested the existence of a prothrombotic state in NAFLD, which is partially unexplored and whose underlying mechanisms are to date not completely understood. Here, we review the mechanisms involved in the pathogenesis of the prothrombotic state in NAFLD across the progression from the healthy liver through the different stages of the disease. We focused on the possible role of several metabolic features of NAFLD possibly leading to hypercoagulation other than endothelial and platelet activation, such as insulin-resistance, nitric oxide production regulation, and gut microbiota homeostasis. Also, we analysed the involvement of plasminogen activator inhibitor-1 (PAI-1) and thromboinflammation taking place in NAFLD. Finally, we described factors striking a prothrombotic imbalance in NASH cirrhosis, with a particular focus on the pathogenesis of portal vein thrombosis. Graphical abstract: Unlabelled Image Highlights: NAFLD could be associated with atherothrombosis and thromboembolism. This association seems to be independent of obesity, diabetes, and hyperlipidaemia. Metabolic features of NAFLD may lead to a prothrombotic state and hypercoagulation. Increased PAI-1 levels and inflammation support the prothrombotic state in NAFLD. NASH-cirrhosis is associated with a high rate of systemic thrombosis and the portal system.